(untitled) (Fiep Bulletin - online, 2015)
The definition of the term sporting talent has been used to characterize people high endowed biological and psychological capacities, which depending on the social way which you/they are involved. this work had as objective verifies the influence of the height on the performance of the horizontal jump in school children of the state of Santa Catarina, Brazil. For accomplishment of that study random selected a sample of 718 school children with age of 10 years old, being 368 male and 350 female. The data used came from the database composed by 9.689 children and adolescents of the Brazil Sport Project (Proesp/SC), located at the Development and Motor Learning Laboratory - UDESC/CEFID. In order to select children for two group of different height, norms established by of the National Center of Health Statistics NCHS were used. School children of both sexes were into group 1 (25 percentile) and group 2 (75 percentile). After separated the groups, a two samples supposing different variances, with the alpha level of significance of 5% (p <0, 05) was used. A significant difference between the means of the results in the horizontal jump test was found. Considering a possible influence of the relationship of the interaction weight/height for the motor performance of children that the study suggests investigations considering the nutritional state of the children, as well as the influence of the height on the performance in other activities in that age group.